Discovering bisdemethoxycurcumin from curcuma longa rhizome as a potent small molecule inhibitor of human pancreatic alpha-amylase, a target for type-2 diabetes - Ponnusamy, Sudha; Smita S. Zinjarde; Bhargava, Shobha; Rajamohanan, P. R.; RaviKumar, Ameeta (Food Chemistry, 2012)
Curcuma longa rhizome is used extensively in culinary preparations in Far East and South-East Asia. Health benefits of curcuminoids from C. longa as antioxidants, anti-cancer and anti-inflammatory molecules have been well documented. We report here for the first time that Bisdemethoxycurcumin (BDMC) from C. longa, acts as an inhibitor to inactivate human pancreatic alpha-amylase, a therapeutic target for oral hypoglycemic agents in type-2 diabetes. Bioactivity guided isolation of rhizome isopropanol extract led to the identification by HPLC and NMR of BDMC as a lead small molecule inhibitor of porcine and human pancreatic alpha-amylase with an IC50 value of 0.026 and 0.025 mM, respectively. Kinetic analysis revealed that using starch as the substrate, HPA exhibited an uncompetitive mode of inhibition with an apparent K-i of 3.0 mu M. The study gains importance as BDMC could be a good drug candidate in development of new inhibitors of HPA and of functional foods for controlling starch digestion in order to reduce post-prandial hyperglycemia. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: BDMC; Curcuma longa; Human pancreatic amylase; kinetics; Type-2 diabetes

Conversion of dried aspergillus candidus mycelia grown on waste whey to biodiesel by in situ acid transesterification - Kakkad, Hardik; Khot, Mahesh; Smita S. Zinjarde; RaviKumar, Ameeta; Kumar, V. Ravi; Kulkarni, B. D. (Bioresource Technology, 2015)
This study reports optimization of the transesterification reaction step on dried biomass of an oleaginous fungus Aspergillus candidus grown on agro-dairy waste, whey. Acid catalyzed transesterification was performed and variables affecting esterification, viz., catalyst methanol and chloroform concentrations, temperature, time, and biomass were investigated. Statistical optimization of the transesterification reaction using Plackett-Burman Design showed biomass to be the predominant factor with a 12.5-fold increase in total FAME from 25.6 to 320 mg. Studies indicate that the transesterification efficiency in terms of conversion is favored by employing lower biomass loadings. A. candidus exhibited FAME profiles containing desirable saturated (30.2%), monounsaturated (31.5%) and polyunsaturated methyl esters (38.3%). The predicted and experimentally determined biodiesel properties (density, kinematic viscosity, iodine value, cetane number, TAN, water content, total and free glycerol) were in accordance with international (ASTM D6751, EN 14214) and national (IS 15607) standards. (C) 2015 Published by Elsevier Ltd.
Keywords: Aspergillus candidus; Biodiesel; In situ acid transesterification; Plackett-Burman Design; Whey

Gedunin and azadiradione: human pancreatic alpha-amylase inhibiting limonoids from neem (azadirachta indica) as anti-diabetic agents - Ponnusamy, Sudha; Haldar, Saikat; Mulani, Fayaj A.; Smita S. Zinjarde; Thulasiram, Hirekodathakallu; RaviKumar, Ameeta (Plos One, 2015)
Human pancreatic alpha-amylase (HPA) inhibitors offer an effective strategy to lower postprandial hyperglycemia via control of starch breakdown. Limonoids from Azadirachta indica known for their therapeutic potential were screened for pancreatic alpha-amylase inhibition, a known anti-diabetic target. Studies were carried out to reveal their mode of action so as to justify their hypoglycemic potential. Of the nine limonoids isolated/semi-synthesized from A. indica and screened for alpha-amylase inhibition, azadiradione and exhibited potential inhibition with an IC50 value of 74.17 and 68.38 mu M, respectively against HPA under in vitro conditions. Further screening on AR42J alpha-amylase secretory cell line for cytotoxicity and bioactivity revealed that azadiradione and gedunin exhibited cytotoxicity with IC50 of 11.1 and 13.4 mu M. Maximal secreted alpha-amylase inhibition of 41.8% and 53.4% was seen at 3.5 and 3.3 mu M, respectively. Michaelis-Menten kinetics suggested a mixed mode of inhibition with maltopentaose (K-i 42.2, 18.6 mu M) and starch (K-i' 75.8, 37.4 mu M) as substrate with a stiochiometry of 1: 1 for both azadiradione and gedunin, respectively. The molecular docking simulation indicated plausible p-alkyl and alkyl-alkyl interactions between the aromatic amino acids and inhibitors. Fluorescence and CD confirmed the involvement of tryptophan and tyrosine in ligand binding to HPA. Thermodynamic parameters suggested that binding is enthalpically and entropically driven with Delta G degrees of -21.25 kJ mol(-1) and -21.16 kJ mol(-1) for azadiradione and gedunin, respectively. Thus, the limonoids azadiradione and gedunin could bind and inactivate HPA (anti-diabetic target) and may prove to be lead drug candidates to reduce/control post-prandial hyperglycemia.

Role of aliasing and interacting factors in the enhanced production of dehalogenase from Yarrowia lipolytica for degradation of brominated compounds - Vatsal, Aakanksha; Potdar, Chirag; Smita S. Zinjarde; Kumar, V. Ravi; Kulkarni, Bhasker D.; RaviKumar, Ameeta (Journal of Industrial and Engineering Chemistry, 2016)
Use of persistent organobromines for industrial applications has led to their accumulation in environment. Yarrowia lipolytica NCIM 3589, a tropical marine yeast, degrades and detoxifies bromocompounds by an initial hydrolytic step. By optimizing culture conditions with 1-bromodecane as reference compound, the dehalogenase involved was remarkably enhanced 13-fold (384.13 U/ml) by a hybrid statistical Plackett-Burman and Box-Behnken design of experiments. Studies bring out in a novel way the role of aliasing and other masked interactions in growth media factors. Importantly, the enzyme acted on C3-C16 bromoalkanes and bromoaromatics, thereby generalizing the 'green chemistry' applicability of optimized media formulation for biotechnological applications. (C) 2016 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.

4-Phenyl quinoline derivatives as potential serotonin receptor ligands with antiproliferative activity - Joshi, Pranaya V.; Sayed, Alim A.; RaviKumar, Ameeta; Puranik, Vedavati G.; Zinjarde, Smita S. (European Journal of Medicinal Chemistry, 2017)
Antagonists of signaling receptors are often effective non-toxic therapeutic agents. Over the years, there have been evidences describing the role of serotonin or 5-hydroxytryptamine (5-HT) in development of cancer. Although there are reports on the antiproliferative effects of some serotonin receptor antagonists, there are very few investigations related to understanding their structure-activity relationships. In this study, we report the screening of a library of 4-phenyl quinoline derivatives for their antiproliferative activities. Preliminary docking studies indicated that these ligands had the ability to bind to two of the serotonin. receptors, 5-HT1B and 5-HT2B. The results of the in silico experiments were validated by performing in vitro studies on MCF-7 breast cancer cell line. The ethylpiperazine derivatives showed maximum toxicity against this cancer cell line. The compounds inhibited Calcium ion efflux (induced by serotonin) and ERK activation. One of the most active 4-phenyl quinoline derivatives (H3a) also induced apoptosis, thereby, suggesting the use of this scaffold as a potential anticancer drug. (C) 2017 Elsevier Masson SAS. All rights reserved.

Optimization of the in situ transesterification step for biodiesel production using biomass of Yarrowia lipolytica NCIM 3589 grown on waste cooking oil - Katre, Gouri; Raskar, Shubham; Zinjarde, Smita; Kumar, V. Ravi; Kulkarni, B. D.; RaviKumar, Ameeta (Energy, 2018)
The in situ (one-step) acid-catalyzed transesterification step for conversion to biodiesel of biomass from oleaginous yeast Yarrowia lipolytica grown on waste cooking oil (WCO) is studied. The process yield of biodiesel was optimized by investigating effects of various parameters, namely, biomass, methanol, chloroform, catalyst, temperature, time and sonication. A Plackett-Burman statistical design of experiments revealed that biomass is the most significant factor influencing biodiesel (FAME, fatty acid methyl ester) production. Subsequently, a one variable design (OVD) of experiments for increased biomass loadings showed higher yields of FAME with no additional requirement of reactants, solvents or special equipment. The biomass grown on WCO had a lipid productivity of 0.042 g L-1 h(-1) and 4 g of this loading gave a high FAME yield of 0.88 gin 8 hat 50 degrees C with methanol: chloroform (10:1) and acid catalyst (0.2 M H2SO4,1.0 ml g(-1)). The FAME profile had desirable amounts of saturated (32.81%), monounsaturated (36.41%), polyunsaturated (30.59%) methyl esters. The predicted and experimentally determined physico-chemical properties of FAME were found in accordance with specified international standards. Thus, the direct one-pot in situ transesterification reaction using Y. lipolytica biomass grown on WCO provides a high yield of biodiesel with potential applicability while simultaneously addressing the management of this pollutant. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Biodiesel; FAME; In situ transesterification; One -step; Waste cooking oil; Yarrowia lipolytica

Structural and physical analysis of underwater silk from housing nest composites of a tropical chironomid midge - Thorat, Leena; Joseph, Emmanuel; Nisal, Anuya; Shukla, Ekta; RaviKumar, Ameeta; Nath, Bimalendu B. (International Journal of Biological Macromolecules, 2020)
Chironomids are an abundant group of aquatic silk spinning insects. They offer a unique opportunity of silk harvestation without killing them; however, they remained underappreciated models in silk research. Here, we investigate the structural and biomechanical characteristics of silk from the midge, Chironomus ramosus. A combination of microscopic (SEM), spectroscopic (CD and IR), structural (XRD), thermal (DSC and TGA) and mechanical measurement tools and techniques were employed to gain critical insights on midge silk. Maximum yield of silk was obtained from Chironomus in similar to 2.5 h, the shortest time reported among insects. The network of water-insoluble silk fibres possessed the smallest diameter of 110 +/- 35 nm, known for any insect silk, qualifying its superiority in fibre fineness. We demonstrate a cruelty-free silk extraction method in contrast to the conventional violent techniques. Structural characterization indicated coexistence of various secondary conformations, beta sheets being predominant. We compare and contrast these features to well-characterized caddisfly and silk-worm silks and highlight the uniqueness in midge silk that render mechanical stability and potentially contribute to its multi-functionalization. We thus propose Chironomus as an emerging candidate of water-borne silk, especially in the context of the `Peace silk' industry, aiming to develop non-violent methods for silk harvestation from animals. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: biopolymer; Chironomus; Commercial applications; Housing nest composite; Peace silk; Underwater silk

Improvement in serum amylase and glucose levels in diabetic rats on oral administration of bisdemethoxycurcumin from Curcuma longa and limonoids from Azadirachta indica - Ramkumar, Sudha; Thulasiram, V. H.; RaviKumar, Ameeta (Journal of Food Biochemistry, 2021)
Curcuma longa and Azadirachta indica are traditionally used in Indian cuisine and Ayurvedic medicine as nutraceuticals against diabetes. The crude C. longa isopropanol extract, bisdemethoxycurcumin (BDMC), the purified bioactive component from C. longa, and limonoids azadiradione, gedunin from A. indica, are able to inhibit in vitro the antidiabetic target human pancreatic alpha-amylase independently. However, no reports on their in vivo efficacy in animal models exist. Thus, the antidiabetic effect of these orally administered human pancreatic alpha-amylase inhibitors was performed on streptozotocin-induced Sprague-Dawley rats. Initially, the normal rats were treated with test compounds (10-100 mg/kg of body weight) in corn oil (5 ml/kg), and as no lethality was observed in these doses, further studies were carried out with lowest concentration of 10 mg/kg of body weight. A reduction in area under curve (AUC) suggested glucose-lowering effect of these compounds in starch fed diabetic rats. The efficacy study showed a significant improvement in body weight, blood glucose levels, serum amylase, and fructosamine levels as well in other serum parameters associated with diabetes with respect to liver and renal functions. Hence, under in vivo conditions, inhibition of alpha-amylase activity by BDMC and limonoids affirms it as one of the mechanisms of action resulting in reduction of blood glucose levels. Practical applications Bisdemethoxycurcumin from C. longa and limonoids, namely, azadiradione and gedunin, from A. indica are potent inhibitors of the antidiabetic target human pancreatic alpha-amylase. Oral Starch Tolerance Test (OSTT) and 28-day efficacy study to check the effect of these orally administered inhibitors in diabetic rat models showed significant improvements in serum blood glucose and amylase levels as well as in other diabetes related serum parameters, namely, bilirubin, lipids, lactate dehydrogenase, alkaline phosphatase, and urea. The study contributes to understanding the action and efficacy of these pancreatic alpha-amylase inhibitors and suggests a potential role for them as nutraceuticals/therapeutics in management of post-prandial hyperglycemia.
Keywords: ‐ α Amylase inhibitors; Azadiractha indica; BDMC; Curcuma longa; in vivo rat studies; Limonoids

Methyl esters of fungal biomass-derived lipids produced via solid-state fermentation of sugarcane bagasse and assessment as a blend component in diesel fuel. - Khot, Mahesh; RaviKumar, Ameeta; Kumar, V. Ravi (Journal of the American Oil Chemists Society, 2021)

On the use of electronegativity and electron affinity based pseudo-molecular field descriptors in developing correlations for quantitative structure-activity relationship modeling of drug activities - Kunde, Pushkar D.; Ramkumar, Sudha; Kamble, Sanjay P.; RaviKumar, Ameeta; Kulkarni, Bhaskar D.; Kumar, V. Ravi (Chemical Biology & Drug Design, 2021)
For quantitative structure-activity relationship (QSAR) modeling in ligand-based drug discovery programs, pseudo-molecular field (PMF) descriptors using intrinsic atomic properties, namely, electronegativity and electron affinity are studied. In combination with partial least squares analysis and Procrustes transformation, these PMF descriptors were employed successfully to develop correlations that predict the activities of target protein inhibitors involved in various diseases (cancer, neurodegenerative disorders, HIV, and malaria). The results show that the present QSAR approach is competitive to existing QSAR models. In order to demonstrate the use of this algorithm, we present results of screening naturally occurring molecules with unknown bioactivities. The pIC(50) predictions can screen molecules that have desirable activity before assessment by docking studies.
Keywords: drug discovery; electron affinity; Electronegativity; molecular field descriptors; partial least squares; QSAR

Process optimization for biodiesel production using agro-waste substrate - RaviKumar, Ameeta; Bed, Rashmi; Kumar, V. Ravi (Journal of the American Oil Chemists Society, 2022)

Statistical optimization of media for enhancing intracellular lipid content in Yarrowia lipolytica NCIM 3589 grown on waste cooking oil for biodiesel production - Jagtap, Shubhangi Ramling; RaviKumar, Ameeta; Raut, Gouri; Kumar, V. Ravi (Journal of the American Oil Chemists Society, 2022)

Aspergillus terreus variant TB21 wet biomass optimized by in-situ transesterification for biodiesel production - Bed, Rashmi K.; Kumar, V. Ravi; RaviKumar, Ameeta (AMB Express, 2025)
The oleaginous fungus, Aspergillus terreus when subjected to random chemical mutagenesis led to isolation of TB21 variant with improved lipid content (78.1%) as compared to wild type (49.8%). The fungal wet biomass grown on sugarcane bagasse hydrolysate (SCBH) was subjected to one-step in-situ (direct) acid transesterification to optimize its conversion to biodiesel using a 2-level factorial statistical design of experiments. The process optimization revealed that wet biomass and methanol were the most significant factors and in a short reaction time period of 5 min with low methanol: wet biomass ratio (10:1) influenced FAME production Statistical optimization studies showed that TB21 exhibited a higher FAME content of 76.5 and 38.1% (w/w) from wet and dry biomass, respectively when compared to wild type (48.1 and 24.5%). FAME productivity (0.55-1 h-1) and a yield (66 gL-1) were achieved when TB21 was grown on SCBH for 120 h at 30 degrees C. The FAME profile from the wet biomass of TB21 grown on SCBH had desirable amounts of saturated (77.7%), monounsaturated (7.2%), and polyunsaturated (2.4%) methyl esters. Physico-chemical properties of TB21-derived biodiesel were determined, namely, density(0.88 g cm-3), kinematic viscosity (4.1 mm s-2), iodine value (96.82), cetane number (55.31), free fatty acid content (0.15%), total acid number (0.3 NaOH mg g-1), meeting international (ASTM D6751, EN 14214) and Indian (IS 15607) standards. Thus, the direct one-pot in situ transesterification reaction using wet biomass of variant TB21 strain showed improved production and quality of biodiesel with potential large scale application using the low-cost substrate (SCBH).
Keywords: Aspergillus Terreus; Biodiesel; In situ transesterification; Mutant; Statistical optimization; Wet biomass